Learning Styles of Gifted Students in Mathematics: A Case Practice in Surkhet District - Bohara, Chhabi Lal (Academic Journal of Mathematics Education, 2021)
This article investigates the learning styles of gifted students in mathematics. For this study, qualitative approach has been used to focus on the experiences of six-mathematics students’ experience studying in secondary level in Surkhet Valley. This article aims to explore the learning styles of gifted students in mathematics and what factors behind adopting in learning. This study utilizes a conceptual framework with seven parameters to check students learning styles in mathematics. For the study, observation, in-depth-interview and document analysis were used to collect the data. This article thus studied six students’ voices, three mathematics teacher and a head teachers’ voice and experiences to explore learning styles of gifted students in mathematics. In conclusion it was found that the self-study and autonomous, goal oriented learning, TPS, schedule based learning and learning mathematics with use of ICT were the learning styles of gifted students. Teacher, parents and administration had pivotal role to motive, mobilize and move to gain desired giftedness.